The youngest occurrence of Hexaprotodon Falconer and Cautley, 1836 (Hippopotamidae, Mammalia) from South Asia with a discussion on its extinction. (10th September 2019) - Jukar, Advait M.; Patnaik, Rajeev; Chauhan, Parth R.; Li, Hong-Chun; Lin, Jih-Pai
Abstract: The earliest hippopotamid fossils from the Indian Subcontinent come from the Miocene of the Siwalik Group. South Asian hippopotamidae are represented by the genus Hexaprotodon, and remains of these hippos are commonly found in Neogene and Quaternary sites. Here we report on the first directly dated specimen of Hexaprotodon sp. from the Narmada Valley of Central India and its associated paleoecological implications. The specimen, an upper right canine fragment, was dated to 16, 467–15, 660 cal BP using accelerator mass spectrometry radiocarbon dating method. This individual lived during Heinrich Event 1, a particularly arid period. Isotopes from dental enamel revealed this animal to have lived in a savanna environment, and likely experienced a shortage of water. Using other dated remains of Hexaprotodon from the Indian Subcontinent, we developed a tentative extinction chronology, which showed that Hexaprotodon likely survived into the Early Holocene. We hypothesize that a combination of climatic stress and anthropogenic impacts would have caused the species' eventual extinction.